The Arabidopsis Rab GTPase family: another enigma variation. - Rutherford, S; Moore, I (2002)
The Arabidopsis genome sequence reveals that gene families such as the Rab GTPase family, which encodes key determinants of vesicle-targeting specificity, are considerably more diverse in plants and mammals than in yeast. In mammals, this diversity appears to reflect the complexity of membrane trafficking. Phylogenetic analyses indicate that, despite its large size, the Arabidopsis Rab family lacks most of the Rab subclasses found in mammals. The Arabidopsis Rab family has, however, undergone a distinct 'adaptive radiation' that has given rise to proteins that may perform plant-specific functions.